MxB/Mx2: the latest piece in HIV's interferon puzzle - Fackler, Oliver Till; Keppler, Oliver Till (EMBO reports, 2013)
Three groups have recently shown in Nature and Cell Host & Microbe that MxB/Mx2 is an interferon-inducible HIV restriction factor, adding to the innate arsenal of the cell against the virus and paving the way for the possible development of new antiviral strategies.
Gesehen am 19.02.2021